Supplemental seed increases native seedling establishment in roadside prairie restoration. Issue 6 (6th April 2018) - Riebkes, Jessica L.; Sherrard, Mark E.; Jackson, Laura L.
Abstract : Tallgrass prairie restorations are plagued by high seed costs and low rates of seedling establishment. Many restorations suffer high rates of seed loss to granivores; yet to date, there are no established protocols to minimize their impact. In this study, we tested whether the application of supplemental (sacrificial) seed reduces native seed consumption and increases native seedling establishment in roadside prairie restoration. We applied supplemental birdseed to a random subset of research plots at three roadside prairie restoration sites and compared rates of seed consumption and early native seedling establishment between supplemental seed plots and control plots. All three roadside restorations were seeded in fall 2014, immediately following the first frost. To assess native seed consumption, we monitored rates of seed removal from "seed cards" during the first 14 days of the restorations. To assess early seedling establishment, we identified and counted all native seedlings in mid‐July of the first restoration year. The application of supplemental seed did not reduce rates of seed consumption, which were very low during the early stages of these restorations, but did increase native seedling establishment. Native seedling establishment was approximately 37% higher in supplemental seed plots than in control plots across restoration sites. The application of supplemental seed may have increased seedling establishment by reducing consumption of native seed during winter and spring. Our results suggest that supplemental seed is a practical, inexpensive technique for increasing seedling establishment in roadside prairie restoration.